Roads to health : infrastructure and urban wellbeing in later medieval Italy - Geltner, G. (Guy), 1974- (Middle Ages series., 2019)
In 'Roads to Health', G. Geltner demonstrates that urban dwellers in medieval Italy had a keen sense of the dangers to their health posed by conditions of overcrowding, shortages of food and clean water, air pollution, and the improper disposal of human and animal waste. He consults scientific, narrative, and normative sources that detailed and consistently denounced the physical and environmental hazards urban communities faced: latrines improperly installed and sewers blocked; animals left to roam free and carcasses left rotting on public byways; and thoroughfares congested by artisanal and commercial activities that impeded circulation, polluted waterways, and raised miasmas. However, as Geltner shows, numerous administrative records also offer ample evidence of the concrete measures cities took to ameliorate unhealthy conditions. Toiling on the frontlines were public functionaries generally known as viarii, or "road-masters," appointed to maintain their community's infrastructures and police pertinent human and animal behavior. Operating on a parallel track were the camparii, or "field-masters," charged with protecting the city's hinterlands and thereby the quality of what would reach urban markets, taverns, ovens, and mills.